The Impact of the Geologic History and Paleoclimate on the Diversification of East African Cichlids - Danley, Patrick D. (Hindawi Publishing Corporation, 2012)
The cichlid fishes of the East African Great Lakes are the largest extant vertebrate radiation identified to date. These lakes and their surrounding waters support over 2,000 species of cichlid fish, many of which are descended from a single common ancestor within the past 10 Ma. The extraordinary East African cichlid diversity is intricately linked to the highly variable geologic and paleoclimatic history of this region. Greater than 10 Ma, the western arm of the East African rift system began to separate, thereby creating a series of rift basins that would come to contain several water bodies, including the extremely deep Lakes Tanganyika and Malawi. Uplifting associated with this rifting backponded many rivers and created the extremely large, but shallow Lake Victoria. Since their creation, the size, shape, and existence of these lakes have changed dramatically which has, in turn, significantly influenced the evolutionary history of the lakes' cichlids. This paper reviews the geologic history and paleoclimate of the East African Great Lakes and the impact of these forces on the region's endemic cichlid flocks.